2006
DOI: 10.1007/s11182-006-0150-5
|View full text |Cite
|
Sign up to set email alerts
|

Special features of thermal evaporation of rare-earth metals

Abstract: The process of thermal evaporation of rare-earth metals (Ce-Yb) with an incomplete 4f-shell is discussed in terms of electronic structure of their surface. Evaluation of the surface density of neutral intrinsic atoms determining the evaporation process is made. The fact of detachment of Sm atoms in the lowest excited 4f 5 5d6s 2 -state from the surface is experimentally demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…The ancient famous Chinese military strategist and philosopher Sun Tzu showed that it was not a great skill "to win one hundred victories in one hundred battlesˮ, but "to subdue the enemy without fightingˮ (Oxford 2017, Tzu n.d.). More recently, the so-called Gerasimov doctrine (Gerasimov 2014, Military Review 2016 refers to a new type of war, going "way beyond the use of military hardware aloneˮ, in other words, "a shift towards the use of non-military means and non-traditional domains, such as youth groups, cyber-attacks, civil media and proxy forcesˮ (Selhorst 2016). In this context, information warfare is considered to be "the starting point of every action now called the new type of warfare, or hybrid war, in which broad use will be made of the mass mediaˮ (Chekinov andBogdanov 2015 apud Giles andSeaboyer 2019, 6).…”
Section: Preliminary Aspectskey Information-related Concepts and Secu...mentioning
confidence: 99%
“…The ancient famous Chinese military strategist and philosopher Sun Tzu showed that it was not a great skill "to win one hundred victories in one hundred battlesˮ, but "to subdue the enemy without fightingˮ (Oxford 2017, Tzu n.d.). More recently, the so-called Gerasimov doctrine (Gerasimov 2014, Military Review 2016 refers to a new type of war, going "way beyond the use of military hardware aloneˮ, in other words, "a shift towards the use of non-military means and non-traditional domains, such as youth groups, cyber-attacks, civil media and proxy forcesˮ (Selhorst 2016). In this context, information warfare is considered to be "the starting point of every action now called the new type of warfare, or hybrid war, in which broad use will be made of the mass mediaˮ (Chekinov andBogdanov 2015 apud Giles andSeaboyer 2019, 6).…”
Section: Preliminary Aspectskey Information-related Concepts and Secu...mentioning
confidence: 99%